[Romházy 1.]
1937-1939: speed racing, horses on the Hortobágy plain, cityscapes of Esztergom, the hungarian Army in Kassa (Kosice), scating rink and inner life of the St.Margit school- Budapest, religious ceremony in Zirc, graduating ceremony in the St.Margit school-Budapest